Risk of multidrug resistance in Escherichia coli associated with routine antimicrobial prophylaxis on pig farms - Ryohei Toya; Miki Okuno; Yosuke Sasaki; Keisuke Yoshihara; Yuichiro Deguchi; Debora Satie Nagano; Seiji Shimada; Yoshitoshi Ogura (npj Antimicrobials and Resistance)
Abstract Although extensively studied, the association between antimicrobial usage and the emergence of antimicrobial resistance (AMR) in livestock still has unresolved aspects. This study analyzed the genomes of 195 Escherichia coli strains from pigs, a species with high antimicrobial consumption, across five production stages on 13 farms in Japan employing diverse antimicrobial administration strategies. A total of 61 acquired AMR genes (aARGs), spanning 13 distinct antimicrobial classes, were identified. A significant correlation was found between antimicrobial usage and the number of aARGs in E. coli strains. The four farms with the highest usage administered antimicrobials orally as routine prophylaxis during fattening. These farms showed significantly higher proportions of multidrug-resistant (MDR) genotypes at all stages compared to farms without routine prophylaxis. The number of frequently detected aARGs was more strongly correlated with total antimicrobial usage than with the usage of the corresponding antimicrobial classes. Co-occurrence network analysis suggested that genetic linkages among these aARGs may promote co-selection, thereby acting as a driving force in the emergence of MDR strains under routine prophylaxis treatment.